The impact of complementary therapies on dysmenorrhea in young women - Ummah, Tammimin; Ismarwati (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS Complementary treatments have been shown to greatly reduce the intensity of dysmenorrhea pain. The use of medicinal plants, herbal concoctions, or compresses might reduce dysmenorrhea discomfort more effectively than taking medications like mefenamic acid, ibuprofen, piroxicam, etc   ABSTRACT Objective: The study's objective was to obtain latest data on alternative therapy for dysmenorrhea in adolescent females of reproductive age. Materials and Methods: A scoping review was conducted using the PRISMA ScR protocol. A search was conducted on PubMed, Science Direct, and Wiley, yielding 848 studies. Ten literature studies were identified that satisfied the criteria for population, exposure, and outcome. The studies also incorporated inclusion criteria, focusing on women of reproductive age who had dysmenorrhea. Results: Out of 848 articles, 32 were considered potentially relevant and met the inclusion criteria. The articles indicated that teenagers commonly used warm compresses and herbal drinks as supplementary therapies to alleviate dys-menorrhea due to their perceived effectiveness and comfort. Other complement-ary therapies for the condition included massage, relaxation, herbal products, self-care practices, acupuncture, and therapeutic methods. Conclusion: Herbal and warm water compress are the most commonly applied alternative therapies for treating dysmenorrhea.